Penegakan Hukum Korban Bullying di Berbagai Tingkat Sekolah di Indonesia - Oktaviani, Vivih; Dianah, Dianah; Subakhti, Hasanudin; Khalimy, Akhmad (Bacarita Law Journal, 2024)
The purpose of this study is to determine (1) the forms of bullying behavior (2) the factors causing the emergence of bullying behavior (3) the impact of bullying behavior (4) Efforts to handle bullying behavior using WDEP technique reality counseling. This study uses an approach with a clinical case study method. The results showed that 1) The forms of bullying carried out by NM were verbal bullying such as calling, calling by nicknames, and calling with parents' names, and physical bullying such as nudging and pinching. The intensity of NM bullying is 5-6 times a day which is done in the classroom and in the school canteen. Characteristics of victims of bullying NM are female 2) The factors that cause NM to do bullying are from parents, NM's personal self, and NM's association with naughty school friends, and supervision from the school on student activities that is still lacking. 3) The impact of bullying behavior by NM causes his learning achievement to decline and is shunned by his friends. 4) The handling effort is done by using WDEP technique counseling. The results of the treatment showed a decrease in bullying behavior. These changes occur because of a change in awareness within the counselee that focuses on current events or current conditions, on personal strengths or what the counselee wants, and encourages individuals to develop better behavior so that it can be useful for the future for the subject and for society. as well as country.